Recovery Of Zinc from Scrap Steel Using Zinc‐Bromine Battery Technology. Issue 5 (16th January 2023) - Standing, Rhys; Laycock, Christian J.; Lloyd, Gareth; Dinsdale, Richard M.; Guwy, Alan J.
Abstract: Secondary production of steel is known to significantly decrease the CO2 emissions of steelmaking, but only 40 % of steel is produced through recycling, which is made difficult by contamination of scrap resources with nonferrous metals and nonmetal debris. These contaminants include zinc, towards which blast furnace and electric arc systems have a low tolerance (<0.02 wt %). In this work, clean and efficient recovery of zinc from the surface of steel substrates was investigated using a custom‐made low‐cost membrane‐free non‐flow zinc‐bromine battery (ZBB) that enabled rapid and straightforward integration and removal of steel substrates. The electrical performance of the cell was characterized by charge‐discharge profiles, and zinc removal and recovery onto electrodes was characterized by using scanning electron microscopy (SEM) and energy‐dispersive spectroscopy (EDS). Upon discharging, the cell efficiently removed >99.9 wt % zinc from steel surfaces. On recharging the cell, zinc was re‐electroplated onto a carbon foam electrode in an easily recoverable form and with high purity. The process was repeated over 30 cycles to demonstrate robustness. The work shows the importance of the cutoff voltage upon discharging: if less than 0.5 V, the cell co‐extracted iron into the electrolyte solution, affecting cell durability and zinc purity. A two‐stage process for recovering zinc from scrap steel is proposed, illustrating how ZBB technology could enable efficient and clean recovery of zinc from complex scrap steel resources in the steel industry. Abstract : Scrapper's delight : Zinc‐bromine battery (ZBB) technology could enable efficient and clean recovery of zinc from scrap steel and therefore help to increase steel recycling and secondary steel production rates and make the prospects for green steel production more realistic. A two‐stage process for recovering zinc from scrap steel using ZBBs is proposed.